Comparison of the Effects of Articaine and Lidocaine Anesthetics on Blood Pressure after Maxillary Infiltration Technique: A Triple-Blind Randomized Clinical Trial - Amirhossein Moaddabi; Parisa Soltani; Maryam Zamanzadeh; Kamran Nosrati; Mojtaba Mollamirzaei; Mariangela Cernera; Gianrico Spagnuolo (International Journal of Dentistry)
Background. Many dental procedures begin with local anesthesia. Subsequent increase in blood pressure in healthy individuals commonly occurs and may be affected by several factors such as mental and physical stress, painful stimuli, and action of catecholamines present in local anesthetic solutions. The aim of the present study is to compare the effects of 4% articaine with 1 : 100000 epinephrine and 2% lidocaine with 1 : 80000 epinephrine on blood pressure after maxillary infiltration technique. Materials and Methods. In this randomized clinical trial, 102 patients were randomly assigned into two groups. One group received 4% articaine with 1 : 100000 epinephrine and the other group received 2% lidocaine with 1 : 80000 epinephrine for local maxillary infiltration. Systolic and diastolic blood pressure of both groups was determined twice: once before anesthetic injection and once 10 minutes after injection. The data were statistically analyzed using descriptive statistics, Shapiro–Wilks test, Levene test, chi-square test, independent t-test, and paired t-test. Results. The mean systolic blood pressure after anesthetic injection in the articaine and lidocaine groups was 125.00 ± 5.67 and 123.16 ± 6.417 mmHg, respectively, showing no statistically significant difference (p=0.127). The mean diastolic blood pressure after injection was 85.02 ± 7.331 in the articaine group and 81.35 ± 12.815 mmHg in the lidocaine group. These values show no statistically significant difference (p=0.080). In both groups, the mean systolic and diastolic blood pressures have increased significantly (p<0.001). Conclusion. Articaine can be regarded as a suitable alternative for lidocaine for maxillary local infiltration, as no significant difference was observed between the effects of the two anesthetic solutions on blood pressure.